2017
DOI: 10.2147/ijn.s132162
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a biophysical model to optimize endoscopic targeting of magnetic nanoparticles for cancer treatment

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) may be used for local tumor treatment by coupling them to a drug and accumulating them locally with magnetic field traps, that is, a combination of permanent magnets and coils. Thereafter, an alternating magnetic field generates heat which may be used to release the thermosensitively bound drug and for hyperthermia. Until today, only superficial tumors can be treated with this method. Our aim was to transfer this method into an endoscopic setting to also reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Accordingly, Roeth and colleagues aimed at translating this strategy to an endoscopic setting and reach tumors deep within the body. 242 They built a biophysical model to find the ideal endoscopic magnetic field trap that accumulates the most SPION. By simulation, they were able to enhance the efficiency of the magnetic field traps by 38-fold in prostate and 8-fold in esophageal cancer models.…”
Section: Magnetic Guidance Of Magnetic Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Roeth and colleagues aimed at translating this strategy to an endoscopic setting and reach tumors deep within the body. 242 They built a biophysical model to find the ideal endoscopic magnetic field trap that accumulates the most SPION. By simulation, they were able to enhance the efficiency of the magnetic field traps by 38-fold in prostate and 8-fold in esophageal cancer models.…”
Section: Magnetic Guidance Of Magnetic Particlesmentioning
confidence: 99%
“…Their method was able to reach tumors inside the body in a minimal-invasive way. 242 In another study, the group of Zhang 243 developed a novel real-time imaging-based guidance system with the aim of improving SPION transport across the BBB and into brain tumor regions. 243 They used an electromagnetic actuator and low-amplitude-excitation-field magnetic particle imaging (MPI) for the simultaneous noninvasive NM guiding and tracking inside a tube.…”
Section: Magnetic Guidance Of Magnetic Particlesmentioning
confidence: 99%
“…Such low concentrations were achieved for a mouse tumor model using permanent magnets. Most promising recent developments showed that by using an endoscopic setting of magnetic targeting the target efficiency could be enhanced by a factor of 40 28 . Consequently, for tumors that can be reached endoscopically, such as PDAC, the MNP concentration inside the tumor could be drastically enhanced in the future using magnetic targeting settings.…”
Section: Introductionmentioning
confidence: 99%
“…The physical absorption and chemical bonding have been used for loading of different molecules on organic and inorganic bases: the tumor-recognition moieties, 71,72 cell-penetrating peptides for MRI applications, 73,74 as well as enzymes, 75 genes, 76-80 growth factors, 81,82 radionucleotides, 83,84 drugs, 85,86 tamoxifen, 87 cefradine, 88 ammonium glycyrrhizinatezz, 89 fludarabine, 90 cisplatin and gemcitabine, 91 amethopterin, 88,92 mitomycin, 93 paclitaxel, 94,95 diclofenac sodium, 96,97 and Adriamycin 98 for drug delivery applications (Figures 2 and 3). 99…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%